Incidence and factors associated with adverse drug reactions in a cohort of individuals starting dolutegravir or efavirenz (Research, Society and Development, 2022)
Prospective cohort of people living with HIV who started combination antiretroviral therapy (cART) with regimens containing efavirenz (EFV) or dolutegravir (DTG) in three specialized HIV/AIDS care services in Belo Horizonte, Brazil, with the objective of analyzing incidence, time to development and factors associated with the first adverse drug reaction (ADR). Data were collected from September 2015 to October 2018 through face-to-face interviews, clinical records, and information systems. The ADR-associated factors were evaluated with Cox regression and the time to the first ADR with Kaplan-Meier survival curves. Among the 433 individuals included, 217 (50.1%) had ADR in 12 months of follow-up. Among the 695 registered ADRs, 604 (86.9%) occurred in individuals using the EFV-based regimen, and gastrointestinal, psychiatric, and nervous system disorders were the most frequent. The mean time to develop the first ADR was 210.6 days (95% CI: 195.5-225.8). The concomitant use of other medications was associated with a higher risk of ADR (HR: 2.00; 95% CI: 1.38-2.89). The use of alcohol (HR: 0.64; 95% CI: 0.49-0.85) and the DTG-based regimen (HR: 0.40; 95% CI: 0.28-0.58) were factors associated with a lower risk of ADRs. We conclude that the DTG-based regimen had a better safety profile than the EFV-based regimen at 12 months of follow-up. Clinical and behavioral characteristics were associated with higher ADR risks and should be monitored when managing the treatment of HIV.